BRIDGING THE GAP IN EMI: A BOTTOM-UP APPROACH TO POLICY AND PRACTICE - Siddikjonova Ugiloy Ibrohimjon kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
English Medium Instruction (EMI) has become increasingly prevalent in higher education globally, yet a persistent gap between top-down institutional policies and bottom-up classroom realities continues to challenge its effective implementation. This paper reports on a qualitative study examining the EMI-related challenges experienced by 183 students across various academic courses through an open-ended questionnaire. Using an inductive coding approach, eight categories of challenges were identified, including vocabulary and terminology difficulties, academic writing challenges, content comprehension issues, communication barriers, difficulties with lecturers' accents, information overload, and miscellaneous institutional challenges. Approximately 23.5% of participants reported no difficulties. Drawing on Spolsky's three-dimensional framework of language policy—language practices, language beliefs, and language management—the findings reveal significant misalignments between EMI policy aspirations and lived student experiences. The paper concludes with targeted recommendations for policymakers and university administrations, advocating for a shift from a 'language-as-medium only' model towards a 'language-as-support-for-learning' approach.